Preferensi Pengguna Kendaraan Pribadi dalam Memilih Jenis BBM Subsidi dan Non Subsidi - Setiawan, Andrian; Putra, Sasana; Purba, Aleksander (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
Gasoline is an important item and becomes a basic need for the community. Subsidized gasoline in Bandar Lampung experienced sales restrictions according to the specified quota. The price of subsidized gasoline which is cheaper than non-subsidized gasoline makes people willing to wait to get subsidized gasoline. This study aims to determine the factors that influence the selection of gasoline types and determine the preferences of each private vehicle user in choosing gasoline, both subsidized gasoline and non-subsidized types. This research uses AHP (Analytical Hierarchy Process) methodBased on the results of the analysis conducted on the group of civil servants, non-civil servants and students, it was found that the group of non-civil servants chose Premium which was the most priority with a weighting value of 0.3745, then for Pertalite of 0.3156 and Pertamax 0.3108. Then for the group of civil servants, the greatest or priority results were Premium with a value of 0.3457, then Pertamax with a value of 0.3350 and Pertalite with a value of 0.3205. Then, for the Student group the most priority results are Premium of 0.3479, then Pertalite of 0.3288 and Pertamax with a difference not too far at 0.3263.